(untitled) (XXI Century. Spanish Literature and Culture, 2013)
An autobiographical work of Manuel Rivas is studied through the three stages that writing crosses: Storyboard (2010), a collection of articles, As voces baixas (2012), the first novel transposition in Galician and Las voces bajas (2012), author’s self-translation in Castilian. Throughout the writing process and in the course of genres and languages, self-referential narrative reveals proficuos elements for reflection on the determination, perspective and vision of the “I” in the present Narrative.